2016
DOI: 10.1073/pnas.1601243113
|View full text |Cite
|
Sign up to set email alerts
|

Placebo effects in cognitive training

Abstract: Although a large body of research shows that general cognitive ability is heritable and stable in young adults, there is recent evidence that fluid intelligence can be heightened with cognitive training. Many researchers, however, have questioned the methodology of the cognitive-training studies reporting improvements in fluid intelligence: specifically, the role of placebo effects. We designed a procedure to intentionally induce a placebo effect via overt recruitment in an effort to evaluate the role of place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
184
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(193 citation statements)
references
References 39 publications
5
184
3
1
Order By: Relevance
“…To date, only a handful of studies have investigated the placebo effect in the cognitive domain245354, and even fewer studies deal with healthy persons55565758. Only one study investigated the possible biological systems involved in the generation of cognitive placebo effects by examining PD patients24.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only a handful of studies have investigated the placebo effect in the cognitive domain245354, and even fewer studies deal with healthy persons55565758. Only one study investigated the possible biological systems involved in the generation of cognitive placebo effects by examining PD patients24.…”
Section: Discussionmentioning
confidence: 99%
“…This creates an expectation of better performance following training, which is known to create positive cognitive outcomes. Indeed, participants who enrolled in a trial of CCT via a flyer suggesting CCT will improve working memory and fluid intelligence had greater post-training performance than participants who enrolled via a non-suggestive flyer, despite participating in the same program (Foroughi et al, 2016). Similarly, in a trial of healthy adults randomly assigned to a placebo pill or no-pill condition, those who took the placebo pill described as a “cognitive enhancer” had greater performance on tests of attention and delayed recall, though no effect was found in five secondary outcome measures (Oken et al, 2008).…”
Section: Expectancymentioning
confidence: 99%
“…A recent study showed that simply telling participants on recruitment flyers that they will participate in a BBrain Training & Cognitive Enhancement^study is associated with stronger transfer effects and an increase in IQ of 5-10 points after just 1 h of cognitive training (Foroughi et al 2016). Therefore, participants in both groups may have performed better at posttest without an actual benefit to working memory capacity.…”
Section: Why Was There a Main Effect Of Time?mentioning
confidence: 99%